ANALISIS HUKUM ISLAM TERHADAP PERPRES NO 20 TAHUN 2018 TENTANG PENGGUNAAN TENAGAKERJA ASING (STUDI TERHADAP PASAL 9 PERPRES NO 20 TAHUN 2018 (PENGGUNAAN TENAGA KERJA ASING) - Sartika trirahmadhini; Muhammad Iqbal Fasa; A. Khumaidi Ja’far (EKSYA : Jurnal Ekonomi Syariah, 2021)
Presidential Regulations can be interpreted as laws and regulations made by the President. Then, the content of the Presidential Regulation is material ordered by law or material to implement government regulations. Meanwhile, foreign workers in terms of law are workers who are foreign citizens holding visas with the intention of working in the territory of Indonesia. in the use of foreign workers contained in Presidential Regulation No. 20 of 2018 concerning the use of foreign workers, this study of article 9 defines the Ratification of the Plan for the Use of Foreign Workers or RPTKA as a permit to employ foreign workers or IMTA. The formulation of the problem in this study is how the construction of the provisions of Article 9 regarding the use of foreign workers in Presidential Decree no. 20 of 2018. and how is the construction of the provisions of article 9 regarding the use of foreign workers in Presidential Decree No. 20 of 2018 in the perspective of Islamic law. while the purpose of this study is to find out how the construction of provisions on article 9 regarding the use of foreign workers in Presidential Decree no. 20 of 2018. and to find out how the construction of provisions on article 9 regarding the use of foreign workers in Presidential Decree No. 20 of 2018 in the perspective of Islamic law. This study uses library research, namely research with data obtained from the literature of primary and secondary books.